Case Report: Unexpected Remission From Extreme and Enduring Bulimia Nervosa With Repeated Ketamine Assisted Psychotherapy - Ragnhildstveit, Anya; Jackson, Laura Kate; Cunningham, Sarah; Good, Linda; Tanner, Quinn; Roughan, Matthew; Henrie-Barrus, Patricia (Frontiers in Psychiatry, 2021)
Background: Bulimia nervosa is a disabling psychiatric disorder that considerably impairs physical health, disrupts psychosocial functioning, and reduces overall quality of life. Despite available treatment, less than half of sufferers will achieve recovery and approximately a third will become chronically ill. Extreme and enduring cases are particularly resistant to first-line treatment, namely antidepressants and cognitive behavioral therapy, and have the highest rate of premature mortality. Here, we demonstrate that in such cases, repeated sessions of ketamine assisted psychotherapy (KAP) can be an effective treatment alternative for improving symptoms. Case Presentation: A 21-year-old woman presented with extreme and enduring bulimia nervosa. She reported recurrent binge-eating and purging by self-induced vomiting 40 episodes per day, which proved refractory to both pharmacological and behavioral treatment at the outpatient, residential, and inpatient level. Provided this, her physician recommended repeated KAP as an exploratory and off-label intervention for her eating disorder. The patient underwent three courses of KAP over three months, with each course consisting of six sessions scheduled twice weekly. She showed dramatic reductions in binge-eating and purging following the first course of treatment that continued with the second and third. Complete cessation of behavioral symptoms was achieved three months post-treatment. Her remission has sustained for over one year to date. Conclusions: To our knowledge, this is the first report of repeated KAP used to treat bulimia nervosa that led to complete and sustained remission, a rare outcome for severe and enduring cases, let alone extreme ones. Additionally, it highlights the degree to which KAP can be tailored at the individual level based on symptom severity and treatment response. While its mechanism of action is unclear, repeated KAP is a promising intervention for bulimia nervosa that warrants future research and clinical practice consideration.